PERAN MEREK SEBAGAI VARIABEL MEDIATOR TERHADAP LOYALITAS PELANGGAN: STUDI KASUS PELANGGAN BTS MEAL DI JABODETABEK - Hendratmoko (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
Brands and products contribute to customer loyalty. The purpose of this study: to analyze how the influence of brand, product, halal, and customer satisfaction on BTS meal customer loyalty in the Jabodetabek area; analyze the role of the brand as a mediator variable between product, halal, and customer satisfaction on customer loyalty BTS meal in the Jabodetabek area. This study uses a quantitative approach. The research was conducted on 12-23 June 2021 with as many as 100 student respondents in the Greater Jakarta area. Sampling by purposive sampling. The results of the study revealed that brands and products have a significant influence on customer loyalty to BTS meals. Brands play a role as a full mediation, especially in the relationship between customer satisfaction and customer loyalty to BTS meals. The influence of brands and products is very significant on customer loyalty to a product. To obtain, maintain and develop loyal customers, companies must continue to improve product quality and carry out brand development and strengthening strategies. Keywords: Loyalty, Brand, Product, Full Mediation